Redes neuronais artificiais estruturadas para alocação online de autoestruturas - COELHO, Bruno França (2019)
To improve the stability performance and the response form of MIMO systems, control of the modes is relevant to impose the design specifications. A bioinspired method for online eigenstructure assignment for the design of multivariable control systems is presented in this paper. The method is based on artificial neural networks for the execution of the control law and for training the controller gains by state feedback. Aiming online tuning of state space controllers, the gain matrix that satisfies all the design specifications, a proposal is presented to compute the gain matrices that best meet a given operating range of MIMO dynamic systems. The proposal is evaluated in two multivariate systems, the first is a mathematical model that represents a fourth-order RLC circuit with two input voltages and two controllable voltage levels, and second model represents the lateral-directional control of an F-16 aircraft.